Roh Kudus sebagai Aktor Utama dalam Kisah Para Rasul (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study explores the role of the Holy Spirit as the main actor in spreading the gospel according to the Book of Acts and its relevance to the church's current mission strategy. Through a qualitative-descriptive approach with literature review, this study examines biblical texts and theological literature that emphasize that since the events of Pentecost, the Holy Spirit has been the main initiator of the church's mission movement. In Luke's narrative, the Holy Spirit not only empowers the disciples to witness, but also leads the direction of ministry, selects and sends missionaries, opens and closes mission paths, and affirms the inclusiveness of the gospel for non-Jewish nations. The Holy Spirit acts as a catalyst that transforms a weak community of disciples into a church that boldly proclaims the gospel, as seen in Peter's sermon and the rapid growth of the congregation. In addition, the Holy Spirit preserves the purity of the church, unites the congregation, and gives spiritual gifts for the building up of the body of Christ. The results of this study confirm that the success of the early church's mission did not depend on human strategies, but on obedience to the Holy Spirit's leadership. The implication for the church today is the need to depend on the work of the Holy Spirit in evangelism, fellowship, and the development of the congregation's gifts, so that the church is able to respond to the challenges of the times with divine power and wisdom.